The acoustic and electroglottographic methods of determination the vocal folds vibration fundamental frequency - Wszołek, Wiesław; Kłaczyński, Maciej; Engel, Zbigniew (Archives of Acoustics, 2007)
There are many methods of measuring fundamental frequency of vocal folds’ vibrations. The mentioned function can be estimated in several ways, either through internal measurements (optical methods) or external measurements (the acoustic analysis of the voice, electric method). Electric methods (EGG), based on analysis of the electroglottographic signal are often applied. However acoustic methods or registration and processing the speech signals can be applied. The authors’ research proves that maximum information on phonetic action of larynx can be assembled by delimitation of the fundamental frequency parameters. Thus the exact determination of pitch function makes a priority in the glottal area research. The spectrum character of speech wave is connected with the fundamental frequency (F_0) of human vocal folds vibration. As it is considered, F_0 of the source during voicing contains an abundance of information on the larynx pathology, individual trait, the emotional state and ethnographical origin of speaker. The literature demonstrates only limited research that conducted simultaneous measurement of fundamental frequency by the EGG and with the acoustics methods. The present paper presents results of such research, including simultaneous processing EGG and acoustic data. The analysis of the F_0 function exactitude and the usefulness of these methods were executed too.